2015
DOI: 10.1111/1365-2435.12585
|View full text |Cite
|
Sign up to set email alerts
|

Fewer new species colonize at low frequency N addition in a temperate grassland

Abstract: Summary 1.Biologically reactive nitrogen (Nr) enrichment threatens biodiversity in diverse ecosystems. Previous controlled N addition experiments may overestimate the effects of atmospheric Nr deposition on the rate of species loss, as it has been found that low frequency Nr additions, as used in traditional studies, lead to more rapid biodiversity loss. It remains unclear, however, whether the colonization of new species (gain) or extinction of old species (loss) is the cause of this difference. By independen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
25
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(32 citation statements)
references
References 43 publications
5
25
2
Order By: Relevance
“…However, although all species can potentially colonise our experimental plots, not all species can successfully establish in these plots, especially at higher N levels, where the rate of loss of resident species is higher and the rate of successful colonisation of non‐resident species is lower (Zhang et al . ). Indeed, when considering all experimental plots together, we found that their species composition was significantly influenced by N treatment differences (Mantel test: r = 0.04, P = 0.0004), but not by their spatial differences (Mantel test: r = 0.01, P = 0.1854), indicating the small role of among‐plot dispersal in shaping the local communities.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…However, although all species can potentially colonise our experimental plots, not all species can successfully establish in these plots, especially at higher N levels, where the rate of loss of resident species is higher and the rate of successful colonisation of non‐resident species is lower (Zhang et al . ). Indeed, when considering all experimental plots together, we found that their species composition was significantly influenced by N treatment differences (Mantel test: r = 0.04, P = 0.0004), but not by their spatial differences (Mantel test: r = 0.01, P = 0.1854), indicating the small role of among‐plot dispersal in shaping the local communities.…”
Section: Discussionmentioning
confidence: 97%
“…This experiment was initially designed to assess how the frequency and rate of N addition affect grassland community structure and ecosystem functioning (Zhang et al . , , ,b, ), and is used here to explore how increased N deposition influences ecosystem stability across spatial scales.…”
Section: Methodsmentioning
confidence: 99%
“…There were about 50 vascular plant species, averaging eight species per m 2 in the control plots across 2008–2013 (Zhang et al . , ). This ecosystem had received no fertilizer or mowing before this experiment.…”
Section: Methodsmentioning
confidence: 99%
“…Smirn., which together accounted for more than 60% of the total above-ground biomass . There were about 50 vascular plant species, averaging eight species per m 2 in the control plots across 2008-2013 (Zhang et al 2014(Zhang et al , 2016b. This ecosystem had received no fertilizer or mowing before this experiment.…”
Section: S T U D Y S I T Ementioning
confidence: 99%
“…The species richness was defined as the number of plant species in the quadrat. Species frequency was defined as the occurrence proportion of one plant species in the quadrats, and calculated as described by Zhang et al (2016). If a species was present in the all eight plots (eight repetitions per treatment) at a treatment in a year, the average frequency of this species was taken as 1 (100%).…”
Section: Field Experiments Nomentioning
confidence: 99%